Food (in)security and the price of rice self-sufficiency - Roehlano M. Briones (Philippine Institute for Development Studies (PIDS), 2016)
The commonly touted solution to achieve food security has always been articulated as achieving self-sufficiency in rice. Since the 1960s, various government regimes have articulated strategies and executed actions to achieve this much-vaunted goal. It has been over half a century, but we have yet to realize this dream. At this point, looking at the hard facts and the numbers, the picture it paints is not pretty. Achieving rice self-sufficiency comes with a price, and let us take a sober look at what it really costs.
Keywords: 330; Philippines; food security; agriculture; rice production; rice; rice self-sufficiency; farming